Bioavailability of Dissolved Organic Phosphorus in Temperate Lakes - Thompson, Seth K.; Cotner, James B. (Frontiers in Environmental Science, 2018)
Freshwater aquatic systems are biogeochemical hotspots, with heterotrophic bacteria rapidly cycling the compounds that pass through them. P is a key nutrient that controls primary production in many freshwater ecosystems and is important for understanding eutrophication in lakes. Previous work has often focused on the dynamics of inorganic phosphorus and its impact on primary production, however, the role of nutrients bound in more complex organic forms (such as dissolved organic phosphorus, DOP) in supporting primary production and harmful algal blooms has been neglected. Here, we quantify the bioavailability of dissolved organic carbon (DOC) and DOP in 27 aquatic systems across the Upper Midwest United States. Using exponential decay models, long-term nutrient degradation assays revealed that decay constants for DOP ranged from- 0.001 per day to -0.12 per day with a median value of -0.01 per day. These rates were geographically variable and were as high or higher than DOC decay constants, which ranged from -0.003 per day to -.024 per day with a median value of -0.01 per day. Additionally, total bioavailability of DOP ranged from 0% to 100% with a median value of 78% of the DOP pool, demonstrating that DOP bioavailability was highly variable across systems. In contrast, bioavailable DOC was more tightly constrained with values ranging from 4.37% to 53.81% of the total DOC pool with a median value of 24.95%. DOP bioavailability was strongly correlated with the DOC:DOP of the organic matter pool, suggesting that bioavailable DOP is drawn down in systems that are more likely to be C limited. Finally, we show that including estimates of DOC and DOP bioavailability reduces estimates of elemental imbalance experienced by aquatic bacteria.